Cell calibration and robot tracking - McMaster, R. S. (1994)
When considering off-line programming of Industrial robots, it is important that the simulated model of the robot and its environment is calibrated against the real hardware. It is well known that industrial robots have relatively good position repeatability characteristics but suffer from a lack of precision in terms of absolute accuracy. When programmed on-line, this is not apparent since the programmer intuitively moves the robot to location points which are relative to the workpiece and other elements within the cell. However, when considering off-line programming using simulation software to represent the robot and its environment, the absolute accuracy of the system becomes a critical issue. The effectiveness of off-line programming is only apparent if there is a true correspondence between the “virtual” simulation system and the “real” hardware system. In order to provide cell calibration, it is important to be able to measure the absolute position of the robot and other strategic locations within the cell. This paper presents details of a measuring system for recording tool point absolute positions and path trajectories. It is intended that this data is then used to improve the correlation between the simulated and the real kinematics of the robot cell.